2017
DOI: 10.1167/iovs.17-21573
|View full text |Cite
|
Sign up to set email alerts
|

Visual Search Behavior in Individuals With Retinitis Pigmentosa During Level Walking and Obstacle Crossing

Abstract: The RP group demonstrated a more active visual search pattern, looking at more areas on the ground in both level walking and obstacle crossing compared with visual normals. This gaze strategy was invariant across conditions. This is most likely due to the constricted visual field and inability to rely on inferior peripheral vision to acquire information from the floor within the environment when walking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“… 40 , 41 Recent work shows that people with retinitis pigmentosa spend an equal amount of time fixating an obstacle in this situation, but they spend less time looking past the obstacle to the path ahead, and a greater amount of time fixating the ground before the obstacle compared with normally sighted controls. 42 When stepping over an obstacle, normally sighted older adults shift gaze to the obstacle earlier and for longer than young adults. 43 , 44 However, spending more time fixating an obstacle when having to avoid it, rather than when having to step over it, is not necessarily an ideal strategy.…”
Section: Discussionmentioning
confidence: 99%
“… 40 , 41 Recent work shows that people with retinitis pigmentosa spend an equal amount of time fixating an obstacle in this situation, but they spend less time looking past the obstacle to the path ahead, and a greater amount of time fixating the ground before the obstacle compared with normally sighted controls. 42 When stepping over an obstacle, normally sighted older adults shift gaze to the obstacle earlier and for longer than young adults. 43 , 44 However, spending more time fixating an obstacle when having to avoid it, rather than when having to step over it, is not necessarily an ideal strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Gaze behaviour was collected at 30 Hz using an SMI iView ETG head mounted mobile eye tracker (version 1.0; SensoMotoric Instruments, Teltow, Germany). Additional information about the eye-tracker system has been published previously 66 . The lenses (used in the blurred group only) were attached to the front, outside of the eye tracker such that it would not influence the eye tracker’s ability to track eye movements.…”
Section: Methodsmentioning
confidence: 99%
“…Each trial was tracked from the frame that the LED above the start pad started flashing (i.e., start of the trial) up to the frame where the hand made contact with the end pad (i.e., end of the trial). The areas of interest were adopted from a previous obstacle crossing study 66 . The following areas of interest were used (see also Fig.…”
Section: Methodsmentioning
confidence: 99%
“…They found that the gaze fixation of participants with low vision was frequently located in a transitional region between various surfaces in addition to an actual surface. Similarly, Timmis et al (2017) compared the gazing behavior of people with low vision and that of fully sighted people navigating an indoor walkway with obstacles on the surface. They reported that people with low vision demonstrated a more active visual search pattern, looking at more areas on the ground than fully sighted people.…”
Section: Previous Studiesmentioning
confidence: 99%